ANALISIS PERSEPSI KEPUASAN PELANGGAN DALAM UPAYA PENGEMBANGAN MUTU PELAYANAN RAWAT INAP DI RS PKU MUHAMMADIYAH GOMBONG - Rizka Fakhriani; Hasnah Rimiyati (Universitas Muhammadiyah Yogyakarta, 2016)
Background: PKU Muhammadiyah Gombong Hospital is Muhammadiyah Business Cahrity in health which is located in Gombong and is facing competition from other healthcare providers. There are some ways to win the competition, by providing value and satisfaction to customers with quality services. Therefore, PKU Muhammadiyah gombong Hospital must improve the quality to maintain patient satisfaction. Objectives: Analyzing the gap betqeen expectation and customer perception of quality at inpatient care in PKU Muhammadiyah Gombong Hospital. Methods: The research is a quantitative research with cross sesctional design. The study was conducted on December 1st to 20th November 2010 in PKU Muhammadiyah Gombong Hospital. The sample obtained was 100 people. The sampling design is a random sampling with proportional strata. The data analysis with different test average in pairs (t-test). Results: The results showed that there are significant gaps between the average expectation and perception (p<0,05). The highest gap score on each dimension contained in the procedure item thoroughly explained the to the patient (the dimension of communication with the gap = - 0,43), hospital wards cleanliness (the dimensions of physical evidence with the gap = - 0,68), nurses never feel busy yo respond to the needs of patients (dimensions of nurse’s attentive with gap = - 0,52), patients feel comfortable while they are in the PKU Muhammadiyah Gombong Hospital (dimension of security with gap = - 0,56), admission (entrance) coped quickly and efficiently by administrative staff (dimension of administrative staff responsiveness with gap = - 0,5), provided sufficient security staff at the hospital (dimension of security with gap = -0,24), and the on time doctors when the ward supervision (dimension of responsiveness doctor with gap = - 0,39). Conclusion: Quality of service in the RS PKU Muhammadiyah Gombong still does not meet customer expectations.